Overview of human health effects related to glyphosate exposure - Galli, Flavia Silvia; Mollari, Marta; Tassinari, Valentina; Alimonti, Cristian; Ubaldi, Alessandro; Cuva, Camilla; Marcoccia, Daniele (Frontiers in Toxicology, 2024)
Glyphosate is a chemical compound derived from glycine, marketed as a broad-spectrum herbicide, and represents one of the most widely used pesticides in the world. For a long time, it was assumed that glyphosate was harmless, either due to its selective enzymatic acting method on plants, and because commercial formulations were believed to contain only inert chemicals. Glyphosate is widely spread in the environment, the general population is daily exposed to it via different routes, including the consumption of both plant, and non-plant based foods. Glyphosate has been detected in high amounts in workers’ urine, but has been detected likewise in bodily fluids, such as blood and maternal milk, and also in 60%–80% of general population, including children. Considering its massive presence, daily exposure to glyphosate could be considered a health risk for humans. Indeed, in 2015, the IARC (International Agency for Research on Cancer) classified glyphosate and its derivatives in Group 2A, as probable human carcinogens. In 2022, nevertheless, EFSA (European Food Safety Authority) stated that the available data did not provide sufficient evidence to prove the mutagenic/carcinogenic effects of glyphosate. Therefore, the European Commission (EC) decided to renew the approval of glyphosate for another 10 years. The purpose of this review is to examine the scientific literature, focusing on potential risks to human health arising from exposure to glyphosate, its metabolites and its commercial products (e.g., Roundup®), with particular regard to its mutagenic and carcinogenic potential and its effects as endocrine disrupter (ED) especially in the human reproductive system.